Influence of the Al content on the phase transformations in Cu-Al-Ag alloys - Adorno, Antonio Tallarico; Benedetti, Assis Vicente; da Silva, Ricardo Alexandre Galdino; Blanco, Matildes (Eclética Química, 2003)
The influence of the Al content on the phase transformations in Cu-Al-Ag alloys was studied by classical differential thermal analysis (DTA), optical microscopy (OM) and X-ray diffractometry (XRD). The results indicated that the increase in the Al content and the presence of Ag decrease the rate of the β1 phase decomposition reaction and contribute for the raise of this transition temperature, thus decreasing the stability range of the perlitic phase resulted from the b1 decomposition reaction.